American grasslands : reckoning with the law and policy that shaped agriculture in the West / Hillary M. Hoffmann. - Hoffmann, Hillary M., 1975- (Cambridge University Press, 2025)
American Grasslands provides a comprehensive review of select laws and policies that have shaped modern western agriculture. Through compelling stories of both famous and lesser-known ranches, the book explores the trajectory of law and policy that has consolidated power in western ranchers and agricultural enterprises. Drawing lessons from historical events such as the Dust Bowl and the current climate and extinction crises, the book illustrates the harmful externalities of agricultural activity and the need for meaningful reform. The book also addresses recent national calls for social and racial justice in the context of western agriculture and public resources like water, land, and wildlife. After highlighting the problems created by current laws and policies, the book offers practical recommendations for future legal and policy reform. American Grasslands is a must-read for anyone interested in the history and future of western agriculture and the role of law and policy in shaping it.